(untitled) (Eurasian Research Bulletin, 2024)
In this article a basic vector method for detecting threats implemented in web systems on the Internet is proposed, in which threats are detected using artificial intelligence, the introduction of the SVM method in the detection of threats, the process of detecting threats, as well as the construction of an IDS/IPS system based on the proposed method done